Frontiers in Optical Methods Nano-Characterization and Coherent Control - Shudo, Ken-ichi.; Katayama, Ikufumui; Ohno, Shin-Ya.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This collection of reviews by leading Japanese researchers covers topics like ultrafast optical responses, terahertz and phonon studies, super-sensitive surface and high-pressure spectroscopy, combination of visible and x-ray photonics. Several related areas at the cutting edge of measurement technology and materials science are included. This book is partly based on well-cited review articles in the Japanese language in special volumes of the Journal of the Vacuum Society of Japan.
State-of-Art of Terahertz Science and Technology -- Broadband Terahertz Spectroscopy and its Application to the Characterization of Thin Films -- Single Photon Counting and Passive Microscopy of Terahertz Radiation -- Coherent Phonons in Carbon Nanotubes -- Time-resolved X-ray Diffraction Studies of Coherent Lattice Dynamics Using Synchrotron Radiation -- Imaging GHz-THz Acoustic Wave Propagation in Thin Films and Microstructures -- Material Evaluation with Various Optical Measurement Systems: Focusing on Terahertz Spectroscopy -- Ultrafast Excitation and Dynamics Measurements with Intense Ultrashort Laser Pulses: High-Order Harmonic Generation from Aligning Molecules and Surface Nanostructuring -- Real Space Mapping of Exciton Interaction Strength in GaN Films by using Four-Wave-Mixing Technique -- Terahertz Light Source Based on Synchrotron Radiation -- Terahertz Synchrotron Radiation; Optics and Application -- Far-infrared Spectroscopy on Solids under Ultra High Pressures -- Real-time Analysis of Initial Oxidation Process on Si(001) by Means of Surface Differential Reflectance Spectroscopy and Reflectance Difference Spectroscopy.
Keywords: Physics; Atoms; Lasers; Photonics; Optics; Optoelectronics; Plasmons (Physics).; Spectroscopy; Microscopy; Microwaves; Optical engineering; Nanotechnology; Physics; Laser Technology, Photonics; Atomic, Molecular, Optical and Plasma Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Spectroscopy and Microscopy; Microwaves, RF and Optical Engineering; Nanotechnology; Electronic books